2019
DOI: 10.3390/w11122461
|View full text |Cite
|
Sign up to set email alerts
|

EU Horizon 2020 Research for A Sustainable Future: INNOQUA—A Nature-Based Sanitation Solution

Abstract: This paper explores the experiences of partners in the multi-national, EU-funded INNOQUA project, who have developed and are currently demonstrating the potential for novel nature-based, decentralised wastewater treatment solutions in ten different countries. Four solutions are under investigation, each at different Technology Readiness Levels (TRLs): Lumbrifilter; Daphniafilter; Bio-Solar Purification unit; UV disinfection unit. An overview of the solutions is provided, along within data from pilot sites. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…An increasing number of studies are testing the effect of earthworms of the genus Eisenia on the sediment permeability, with the aim of introducing them into future filtration systems [91], but few of these studies have demonstrated their application in demonstration pilots or living labs. In parallel, there is a rising number of farms that are developing sewage filtration with the help of lumbriculids in systems called lumbrifilters or lumbricomposters, especially for those farms that produce vegetables by aquapony [92].…”
Section: The Influence Of Biofilm Consumption On Sediment Permeabilitymentioning
confidence: 99%
“…An increasing number of studies are testing the effect of earthworms of the genus Eisenia on the sediment permeability, with the aim of introducing them into future filtration systems [91], but few of these studies have demonstrated their application in demonstration pilots or living labs. In parallel, there is a rising number of farms that are developing sewage filtration with the help of lumbriculids in systems called lumbrifilters or lumbricomposters, especially for those farms that produce vegetables by aquapony [92].…”
Section: The Influence Of Biofilm Consumption On Sediment Permeabilitymentioning
confidence: 99%
“…There are not many reports of the use of this parameter in the selection of TAOs, but it is well known that both Ozone and UV-based technologies have a high TRL compared to emerging technologies such as photo catalysis. Thus, this parameter allows establishing viable application options in a given period of time [36], [37].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Domestic and industrial wastewater treatment requires specific wastewater treatment plants provided with different treatment stages (mechanical, chemical, biological). Modern technological solutions have been developed, applicable to small communities as well as to low-income countries that do not have the necessary financial funds for the construction and operation of large treatment plants [13]. In recent years, major investments have been made using locally funded projects and European funds in certain regions of Romania (EU Cohesion Fund, Operational Program "Environment" "Extension and modernization of water and wastewater systems" [14,15]) regarding the water supply for human consumption, respectively the construction of sewerage systems connected to domestic and industrial wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%